Comparison of early and delayed lumbar disc herniation surgery and the treatment outcome - Ermin Hadžić; Bruno Splavski; Goran Lakičević (Medicinski glasnik, 2021)
Aim: To evaluate the influence of preoperative symptoms duration on surgical outcome of one-level lumbar disc herniation surgery. Methods: In a prospective randomized study, 67 adult patients with one-level lumbar disc herniation were analysed. The patients whose duration of symptoms was <6 months were included in the case group, while those with the duration of symptoms ˃6 months formed the control group. The investigated preoperative variables were: pain intensity in the back and legs (Visual Analogue Scale - VAS), Sciatica Bothersomeness Index (SBI), index of disability (Oswestry Disability Index - ODI). Postoperative variables were: pain intensity in the back and legs (VAS), SBI, ODI, and outcome according to the Odom’s criteria (excellent, good, satisfactory and poor). Significance level was set at p <0.05. Results: A statistically significant difference was recorded between the groups, showing a better decrease of radicular pain intensity and sciatica bothersome, as well as patients disability in the case group (p<0.001). According to the Odom’s criteria the outcome was better in the case group, since the difference between the groups was statistically significant too (p<0.05). Conclusion: Early lumbar disc herniation surgery performed within the first 6 months from the start of symptoms is beneficial due to decreases of radicular pain intensity, sciatica bothersomeness, and patient’s disability.
Keywords: discectomy; intervertebral disc; pain; radiculopathy; syndrome